Education Investment In Economic Growth Following Provinces In Indonesia In 2014-2020 - Dai’ah Dini; Rizqon Halal Syah Aji (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2022)
Education is the main capital in carrying out the development of a country. The purpose of this study is to determine the effect of education investment proxied by the school participation rate (APS) of elementary, middle and high schools on Economic Growth in 34 provinces in Indonesia in 2014-2020. This study used a dynamic panel regression analysis method with a fixed effect model. The results of this study show that the SD variable has a significant influence on economic growth in 4 provinces in Indonesia, namely the provinces of DKI Jakarta, West Java, Central Java, East Java and in 30 other provinces have no significant effect. The SMP variable has a significant influence on Economic Growth in 2 provinces in Indonesia, namely DKI Jakarta, East Java Province and in 32 other provinces has no significant effect. Meanwhile, the SMA variable has a significant influence on Economic Growth in 4 provinces in Indonesia, namely DKI Jakarta, East Java, Banten, East Kalimantan provinces and in 30 other provinces has no significant effect. The education investment variables proxied by the primary, middle and high school budgets together have a significant influence on economic growth in 30 provinces in Indonesia in 2014-2020 and in 4 other provinces such as Riau, Bali, West Nusa Tenggara and Papua have no significant effect.